Neuromuscular Adaptation To Speed Training In Karate: An Interdisciplinary Literature Review - Sudirman (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
Speed is one of the most critical biomotor components in karate, as successful performance in kumite depends on rapid reactions, explosive movements, and efficient execution of offensive and defensive techniques. Recent advances in exercise physiology and neuroscience suggest that speed training induces neuromuscular adaptations that enhance athletic performance through improvements in neural efficiency, motor unit recruitment, and movement coordination. However, evidence regarding these adaptations remains fragmented across multiple scientific disciplines. Objective: This interdisciplinary literature review aimed to synthesize and analyze the conceptual and empirical evidence concerning neuromuscular adaptations resulting from speed training in karate athletes. Methods: A literature review approach was employed by analyzing peer-reviewed articles published between 2015 and 2025 from Scopus, Web of Science, PubMed, ScienceDirect, Google Scholar, and SINTA-indexed journals. A total of 28 eligible studies were selected and analyzed using a narrative synthesis approach focusing on neuromuscular mechanisms and karate performance outcomes. Results: The review revealed that speed-oriented training significantly improved motor unit recruitment (85.7%), rate of force development (78.6%), reaction time (75.0%), intermuscular coordination (71.4%), neural drive enhancement (64.3%), and movement economy (57.1%). Karate-specific speed drills demonstrated the greatest performance improvements, including increases in movement speed (13.4%), rate of force development (17.8%), and reaction time (14.6%). Furthermore, neuromuscular adaptations contributed to improvements in punching speed (15.2%), kicking velocity (14.5%), agility (12.8%), technical accuracy (10.4%), and reactive performance (16.1%). Conclusion: Speed training effectively enhances karate performance through neuromuscular adaptations involving neural plasticity, motor unit activation, intermuscular coordination, and force transmission efficiency. These findings support the integration of neuromuscular-focused speed training into karate conditioning programs to optimize competitive performance.